Development of E-LAPD with Problem Based Learning Oriented to Train Creative Thinking Skills on Reaction Rate Material - Agustine, An Dhini Dwi Nur; Hidayah, Rusly (JIIP - Jurnal Ilmiah Ilmu Pendidikan, 2024)
The purpose of this research is to describe the advisability of the E-LAPD developed, including its validity, practicality, and effectiveness. The type of research used is research and development (R&D) with the 4-D model proposed by S. Thiagarajan, Dorothy S. Semmel, and Melvyn I. Semmel (1974). The data collection method used was observation, questionnaire, and test. The results showed that validity has a mode worth 3 because it has the largest percentage in three criteria (content, construct, and graphics). Practicality received very practical criteria, with a percentage of 97% in the content aspect and 98% in the graphic aspect. Effectiveness received effective criteria, with the outcome of the N-gain score obtained indicating a value of 0.8. Nevertheless, the N-gain score for each creative thinking component shows originality 0.7, fluency 0.82, flexibility 0.86, and elaboration 0.8. This research's finding is that E-LAPD with problem-based learning oriented to train creative thinking skills on reaction rate material is feasible to develop as teaching material.